BENALU SEBAGAI MEDIA UNGKAP DALAM KARYA SENI GRAFIS TEKNIK SERIGRAFI - MASDION, Dr. Budiwirman, M.Pd., Yofita Sandra, S.Pd., M.Pd. (Universitas Negeri Padang, 2018)
The purpose of this work is to visualize the parasitic plant as a medium expressed in serigraphy , taking philosophy from the traits of living parasite from other trees and controlling the tree. The method used in the creation of this final work is a production printing. Every work that writers create is intertwined with each other because it has the same themes, ideas and concepts. After going through a long process then created the final work of the author with 10 titles. : “the King.” “the Political Chair.” “Bekap.” “Unbalanced.” “Provocation.” “Rare.” “Mutually blame.” “Lose.” “Tenth,” “Pawn.” is expected to art students after. Those final works of arts is expected to enhance students appreciation and spirit to do better increating graphic art.Keywords: parasites, artwork, serigraphy techniques